A retomada do romantismo alemão em Kein Ort. Nirgends e Die neuen Leiden des jungen W.: o romance como resistência - Coutinho, Márcio José (2007)
During the seventies, it is possible to verify the arising of a set of works characterized by a tendency on recovering aesthetic elements and values from Romanticism in East-Germany Literature. That country lived under the Socialism imposed by force by the USSR, and the State exerted strong oppression, censorship and repression over people, and also imposed a realistically-based program to be followed by the writers, in order to consolidate the ideological principles of the regime the Socialist Realism, created departing from Georg Lukács conceptions on realism. In response to this context, some literary works can be considered as assuming the role of resistance, by the adoption of non-mimetic forms and techniques of writing. In this sense, this thesis aims at doing a comparative analysis between Christa Wolf s novel Kein Ort. Nirgends and Ulrich Plenzdorf s novel Die neuen Leiden des jungen W., focusing on the possible role of themes as subjectivity, melancholy and turn to past to the political and social aspirations proper of the writers vinculated to this literary tendency. The concept of Romanticism must be understood according to the particular historical meanings resulting with regard to the discussion on cultural and literary heritage. Christa Wolf s, Bertolt Brecht s, Theodor Adorno s, Walter Benjamin s and Anatol Rosenfeld s essays constitute the main critical and theoretical approach used to base this research